Organochlorine Pesticide Residues in Broiler and Desi Chicken Meat of Hyderabad - Kumar, K. Sunil; Fairoze, Nadeem; Muthukumar, M.; Naveena, B. M. (Journal of Meat Science, 2014)
An experiment was conducted to estimate certain organochlorine pesticides (DDT-DichlorodiphenylTrichloroethane, HCH – Hexachloro Cyclo Hexane and Cyclodiene compounds (aldrin, dieldrin, endrin, endrin aldehyde, endosulfan, endosulfansulphate, heptachlor and heptachlor epoxide) residues in meat samples of broiler and desi chicken collected from retail markets of Hyderabad. A total of 60 samples (each 15 meat and fat samples of broiler and desi chicken) were analysed for the presence of organochlorine pesticides (OCPs) residues using a gas chromatograph equipped with an electron capture detector. The percentage of contamination was higher in broiler meat samples (70 percent) compared to desi chicken (6.66 percent). Among the OCPs - DDT, HCH, aldrin, endrin, heptachlor and endosulfan residues were detected in broiler meat where as, only DDT and HCH residues were detected in desi chicken meat. The overall concentration of DDT, HCH, aldrin, endrin, heptachlor and endosulfan residues in broiler meat were 0.101, 0.167, 0.085, 0.035, 0.02 and 0.057 ppm, respectively and the overall concentration of DDT and HCH residues in desi chicken meat were 0.05 and 0.03 ppm, respectively. The study revealed that the market samples of desi chicken meat had lower incidence and levels of residues as compared to that of broiler chicken meat samples and the concentration of pesticide residues in both broiler and desi chicken were higher in fat samples compared to meat samples. Further, the levels of pesticide residues recorded in the study were lower than the maximum residue limit prescribed by Food Safety Standards Regulations (Contaminants, toxins and Residues) 2011.